A Deep Tunneled Architecture For Creating Privacy-Aware Secured Email Communication - T. Jemima Jebaseeli, D Jasmine David; R.Venkatesan (International Journal of Advanced Science and Technology, 2020)
Nowadays online attacks have greater than before and the most general attack in the midst of them is phishing. Phishing is a sort of attack wherein the kind of email trick frequently connected with spam. It takes the private data which is completed by a programmer, so it is particularly significant for the clients to recognize the phony site and abstain from falling prey to it. Subsequently another methodology is proposed and named as an anti-phishing structure dependent on visual cryptography and RSA calculation to take care of the issue of phishing. Here a picture based confirmation utilizing Visual Cryptography (VC) and RSA calculation is utilized. Utilizing cryptography, the mystery instant messages are changed over as a mixed up group then the mail will be sent to the destination. At the receiver end, the received offers are stacked one over another to produce the cover image which has the message content covered up in it. This is done by visual cryptography.